Bioconversion of yellow wine wastes into microbial protein via mixed yeast-fungus cultures - Wenzhe Zhu (2020)
© 2019 Elsevier Ltd The potential for microbial protein production in the mixture of yellow wine lees and rice soaking wastewater was examined. Strong symbiotic effect was observed in fermentation with yeast-fungus mixed culture of Candida utilis and Geochichum candidum at a ratio of 1:1 (v/v). The maximum specific biomass yield of 4.91 ± 0.48 g final biomass/g initial biomass with a protein content of 68.5 ± 1.0% was achieved at inoculum-to-substrate ratio of 10% (v/v) and aeration rate of 1.0 volumeair/volumeliquid/min. The essential amino acids contents of the derived protein were comparable to commercial protein sources with high amounts of methionine (2.87%, based on total protein). The reduction in soluble chemical oxygen demand of 79.4 ± 0.4% was mainly due to uptake of carbohydrate, soluble protein, volatile fatty acids, amino acids, etc. The application of mixed yeast-fungus technology provides a new opportunity for microbial protein production from these low-value organic residue streams.